2021
DOI: 10.1111/1462-2920.15372
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic use of catecholamine neurotransmitters as siderophores to access iron by Pseudomonas aeruginosa

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 73 publications
2
44
0
Order By: Relevance
“…We find that the catecholamine neuromodulators and AR agonists, EPI and NE, promote both the planktonic growth and biofilm forming capacity of this organism, confirming earlier findings that showed norepinephrine increased virulence, motility and adhesion in strains of P. aeruginosa 23,42 . These studies pointed out the possible mechanism to include to chelation of iron by catecholamines for enhancing transport into P. aeruginosa cells possibly through the outer membrane receptor and transporter, TonB 60 . Significantly and newly reported here, the catecholamine growth‐enhancing effects can be reversed when the cultures are treated with the beta‐AR antagonist timolol (TIM).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We find that the catecholamine neuromodulators and AR agonists, EPI and NE, promote both the planktonic growth and biofilm forming capacity of this organism, confirming earlier findings that showed norepinephrine increased virulence, motility and adhesion in strains of P. aeruginosa 23,42 . These studies pointed out the possible mechanism to include to chelation of iron by catecholamines for enhancing transport into P. aeruginosa cells possibly through the outer membrane receptor and transporter, TonB 60 . Significantly and newly reported here, the catecholamine growth‐enhancing effects can be reversed when the cultures are treated with the beta‐AR antagonist timolol (TIM).…”
Section: Discussionsupporting
confidence: 90%
“…This may be related to the receptors that transduce the catecholamine-mediated pyoverdine and pyocyanin responses. Although not fully identified, some potential catecholamine receptors for P. aeruginosa include the TonB Dependent Transporters PirA and PiuA 60 and the interconnected QS systems las, rhl and PQS. 23,71 Alternatively, secreted protein was sampled at 72 h, and longer incubation times may be needed to detect the change in translation of this protein.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have also shown that the presence of xenosiderophores in P. aeruginosa growth media often strongly induces the expression of the proteins of their corresponding uptake pathways. 26,32,35,36,41,45 Here, we first investigated the effect of 0.25 µM hemin on the expression of the TBDT genes hasR, phuR and hxuA, involved in hemin uptake in P. aeruginosa cells, using differential proteomic approaches. The intracellular concentration of hemin in eukaryotic cells is estimated to be between 0.025 and 0.3 µM, 55 and the KD of HasAp for hemin of 350 ± 50 nM, 6 leading us to choose the concentration of 0.25 µM hemin for our experiments.…”
Section: Resultsmentioning
confidence: 99%
“…35 As previously described, our differential proteomic data showed that the presence of 10 µM TCV alone in the medium of PAO1 induces the expression of pfeA (log2 fold change of 4.81), pfeE (log2 fold change of 5.55), and pirA, another TBDT also involved in iron uptake via catechol xenosiderophores, (log2 fold change of 2.05). 26,41,45,67,68 The presence of TCV also resulted in the repression of fptA expression (log2 fold change of -2.37) and that of many genes encoding proteins of the PCH-dependent iron-uptake pathway (Figure 7A). In the presence of both 10 µM TCV and 0.25 µM hemin, the expression of pfeA and pirA was still induced with the same efficiency as with TCV alone.…”
Section: P Aeruginosa Pao1 To the Presence Of Hemin And Xenosiderophoresmentioning
confidence: 98%
See 1 more Smart Citation